Le syndrome Sturge-Weber: à propos d’un cas - Doumiri, Meriem (Pan Afr Med J, 2020)
Sturge-Weber syndrome (SWS) or encephalofacial angiomatosis is a rare neurocutaneous and congenital ocular syndrome. It can cause two malformations: congenital facial capillary planar angioma and leptomeningal venous-capillary angioma (most often parieto-occipital homolateral angioma). Neuroimaging, in particular magnetic resonance imaging (MRI), plays an important role in the diagnosis, ideally before the occurrence of neuro-ocular complications. We report the case of a child in whom SWS was suspected based on facial angioma and pharmaco-resistant epilepsy.